Effect of Wastewater Treatment Efficiency on River Ecosystem Sustainability - Kartikasari, Rina; Rodriguez, Maria L.; Nakamura, Kenji (RESWARA: Jurnal Riset Ilmu Teknik, 2024)
Wastewater treatment plants (WWTPs) play a crucial role in controlling pollutant discharges into river systems, thereby influencing river ecosystem sustainability. However, increasing evidence suggests that conventional and even advanced wastewater treatment processes may not fully mitigate ecological impacts on receiving waters. This study aims to synthesize and critically analyze global scientific evidence on the effects of wastewater treatment efficiency on river ecosystem sustainability, focusing on physicochemical, biological, and metabolic responses. A systematic literature-based research design was employed, analyzing 30 peer-reviewed journal articles, conference proceedings, and preprints published between 2016 and 2024. The reviewed studies reveal that enhanced wastewater treatment efficiency significantly improves water quality, reduces nutrient and micropollutant loads, stabilizes ecosystem metabolism, and supports biodiversity recovery. Nevertheless, residual contaminants, altered flow regimes, and nutrient imbalances persist, leading to changes in microbial communities, food web dynamics, and fish assemblages. The findings indicate that while improved wastewater treatment is essential for achieving river sustainability, current treatment targets remain insufficient in many regions. This study highlights the need for integrated wastewater management strategies that combine advanced treatment technologies, ecological flow considerations, and watershed-scale planning to ensure long-term river ecosystem resilience.